Impact of water droplets on superhydrophobic surfaces with various inclined angles - Ng, Sam Yong Ze (Nanyang Technological University, 2022)
This report investigates the effects of superhydrophobic surface inclination on the impact behaviours of water droplets. Throughout the experiment, two parameters – surface inclination angles and drop release heights – were altered to a set of specified values. An experimental setup utilising a goniometer and retort stand were used to allow for precise adjustments to obtain accurate readings and analysis.